Colecção Berardo 1917 - 1999. - Berardo, José; Kuspit, Donald; Sardo, Delfim; Veiga, Margarida; Centre Cultural de Belém, Lisboa (Lisboa : Centro Cultural de Belém, 2000)
Agar, Eileen ; Albers, Josef ; Andre, Carl ; de Andrea, John ; Anselmo, Giovanni ; Appel, Karel ; Arman ; Arp, Hans (Jean) ; Arroyo, Eduardo ; Art & Language ; Ashkin, Michael ; Bacon, Francis ; Baziotes, William ; Bell, Larry ; Beothy, Etienne ; Bergmann-Michel, Ella ; Bissière, Roger ; Blackwell, Tom ; Blake, Peter ; Bleckner, Ross ; Boetti, Alighiero ; Bonalumi, Agostino ; Boshier, Derek ; Bourgeois, Louise ; Brauner, Victor ; Breton, André ; Brooks, Jason ; Brown, Cecily ; Brun, Christopher Le ; Buchheister, Carl ; Buren, Daniel ; Bury, Pol ; Cahn, Marcelle ; Caro, Anthony ; Chadwick, Lynn ; Chamberlain, John ; Charlton, Alan ; Chia, Sandro ; De Chirico, Giorgio ; Clemente, Francesco ; Cohen, Bernard ; Colombo Filia, Luigi ; Cornell, Joseph ; Cottingham, Robert ; Cucchi, Enzo ; Dali, Salvador ; Deschamps, Gérard ; Dine, Jim ; Doig, Peter ; Domela, César ; Dominguez, Oscar ; Dubuffet, Jean ; Duchamp, Marcel ; Equipo 57 ; Ernst, Max ; Fautrier, Jean ; Federle, Helmut ; Fischl, Eric ; Riverhead (New York) ; Fontana, Lucio ; Francés, Esteban ; Francis, Sam ; Freundlich, Otto ; Fulton, Hamish ; Galan, Julio ; Gober, Robert ; Gorin, Jean ; Gottlieb, Adolph ; Gruber, Francis ; Grünfeld, Thomas ; Gursky, Andreas ; Guston, Philip ; Guttuso, Renato ; Hartung, Hans ; Harvey, Marcus ; Held, Al ; Hélion, Jean ; Henri, Florence ; Herbin, Auguste ; Herold, Jacques ; Hilliard, John ; Hockney, David ; Hugnet, Georges ; Hugo, Valentine ; Humphries, Jacqueline ; Huszar, Vilmos ; Indiana, Robert ; Jacquet, Alain ; Joffe, Chantal ; Jorn, Asger ; Joseph, Peter ; Judd, Donald ; Kacabadzé, David ; Kapoor, Anish ; Kassak, Lajos ; Katz, Alex ; Kawara, On ; Kelly, Ellsworth ; Kiefer, Anselm ; King, Phillip ; Klein, Yves ; Kline, Franz ; Klucis, Gustav ; Knoebel, Imi ; Knudson, Greta ; etc.
biog. p. 304-334 (portugees) p. 336-365 (engels)
Engels
Portugees
Colecção Berardo 1917 - 1999, Centre Cultural de Belém Lisboa, 28 January- 30 April 1999
boek